Antioxidant flavan derivatives from the leaves of Morus alba. (February 2019) - Zhang, Hua-Ran; Li, Ming; Wang, Miao-Miao; Wang, Xiao-Ning; Shen, Tao; Wang, Shu-Qi; Ren, Dong-Mei
Graphical abstract: Highlights: Nine new flavan derivatives were isolated from the leaves of Morus alba. Two pairs of stereoisomers were separated by chiral HPLC. The absolute configurations of five flavans were determined by the comparison of experimental and calculated ECD curves. All of the obtained flavans were potential Nrf2 pathway activators. Abstract: Two pairs of new flavans, moracinflavan A and B (1a/1b and2a/2b ), together with another five new flavan derivatives moracinflavan C–G (3–7 ), and three known flavans (8–10 ) were isolated from the leaves of Morus alba. Their structures were elucidated by detailed analyses based on spectroscopic data. Separation of the stereoisomeric mixtures of1a and1b, 2a and2b was achieved using chiral HPLC, and the absolute configurations of the respective stereoisomers were determined based on comparison of experimental and calculated electronic circular dichroism (ECD) spectra. Using an ARE-dependent luciferase reporter assay, we identified that these flavans were capable of increasing ARE-luciferase activities. This indicated that these flavans are potential Nrf2 activators.